2020
DOI: 10.1016/j.cej.2020.125570
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of UV-induced AOPs (UV/Cl, UV/NHCl, UV/ClO and UV/HO) in the degradation of iopamidol: Kinetics, energy requirements and DBPs-related toxicity in sequential disinfection processes

Abstract: Removal efficiency of iopamidol fol-• The pH behaviors of UV-based AOPs upon iopamidol in 5-9 exhibited quite differently.• UV/Cl 2 and UV/NH 2 Cl enhanced classical DBPs and I-THMs while UV/ClO 2 and UV/H 2 O 2 exhibited elimination effect.• The risk ranking of DBPs-related toxicity was UV/NH 2 Cl > UV/ Cl 2 > UV > UV/H 2 O 2 > UV/ClO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(31 citation statements)
references
References 89 publications
(208 reference statements)
1
30
0
Order By: Relevance
“…Advanced Oxidation Processes (AOPs) have been proposed to be implemented together with the conventional biological treatments to efficiently address the removal of CECs from wastewater [ 12 , 13 , 14 , 15 ]. These processes rely on chemical and/or physical processes generating highly reactive radical species (such as HO ● and SO 4 ●− ) able to react non selectively with the most organic compounds in solution, including, bio-recalcitrant compounds [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced Oxidation Processes (AOPs) have been proposed to be implemented together with the conventional biological treatments to efficiently address the removal of CECs from wastewater [ 12 , 13 , 14 , 15 ]. These processes rely on chemical and/or physical processes generating highly reactive radical species (such as HO ● and SO 4 ●− ) able to react non selectively with the most organic compounds in solution, including, bio-recalcitrant compounds [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…EE/O total includes the components of direct electrical energy (EE/O electricity ) and equivalent electrical energy of the oxidants (EE/O oxidant ). Text S4 provides information on the calculation formulas of EE/O total , EE/O electricity , and EE/O oxidant , while details of the calculations are provided in Table S4. , As presented in Figure c, the EE/O total of the E-PM-PDS process was 1.007 kWh m –3 , which was much lower than that of other processes (5.200–75.701 kWh m –3 ) investigated in this study. The results demonstrated that the E-PM-PDS process improved the oxidation efficiency of target organic pollutants and was also advantageous in terms of energy consumption.…”
Section: Resultsmentioning
confidence: 81%
“…Though the combination of UVC and ClO 2 enhanced the micropollutant abatement via generating more reactive species (e.g., • OH and chlorine radical (Cl • )), they are less effective than the well-documented UVC/H 2 O 2 , UVC/Cl 2 , and UVC/NH 2 Cl AOPs under the same initial oxidant dosages. For example, Tian et al [57] compared the combination of UVC with different oxidants (i.e., Cl 2 , NH 2 Cl, ClO 2 , and H 2 O 2 ) in the degradation of iopamidol and reported the k obs following the order of UVC/Cl 2 (1.9 × 10 −2 s −1 ) > UVC/H 2 O 2 (1.3 × 10 −2 s −1 ) > UVC/NH 2 Cl (1.0 × 10 −2 s −1 ) > UVC/ClO 2 (4.4 × 10 −3 s −1 ) under the same conditions. 22)), which subsequently is activated by UV radiation to produce RCS (i.e., Cl • and chlorine oxide radicals (ClO • )).…”
Section: Reaction Kineticsmentioning
confidence: 99%